Altinópolis : por um projeto de paisagem - Magalhães, Kelly Cristina (2016)
The thesis presents the concept of landscape deconstruction as an alternative to reveal chances of landscape projects for intervention in the territory, and in particular, proposes to its definition as an analytical process and planning instrument in the case of the city of Altinópolis, state of São Paulo. In this approach the landscape of deconstruction in the city of Altinópolis occurs in three categories that enable the analysis in landscape mosaic from an understanding of the relationship timeline Border, Trama and ruin. Runs through the debate between disciplines that have contributed to the latest conceptual outlines of the word landscape, to then be guided by the analysis of the landscape transformation of history, as it emerges from the understanding of a landscape transformation project in constant motion (technical becoming) and the formation of the modern territory. The analysis of favorable material conditions and the perception that these differences and gradations are generating new forms of this landscape (difference), so attention to a historical and return continued the landscape is the ability to print a new thinking about the city and landscape, object of our study.